Theoretical Study of Fractal-Like Kinetics of Adsorption - Hadis Bashiri; Adele Shajari (Adsorption Science & Technology)
In this study, the kinetics of adsorption on the solid surfaces has been studied. Based on the Langmuir rate equation and a fractal-like kinetic model, a new rate equation has been derived. As a proof of concept, we investigated the applicability of the new equation by describing experimental data of adsorption on graphene. The fitting of the obtained equation was compared with fractal-like rate equation of Azizian. In addition, we also compared the newly derived equation with some of the common rate equations such as the Langmuir, pseudo-first-order and pseudo-second-order equations. Our results show that the newly derived equation is superior for describing the kinetic data compared with the aforementioned equations.